PECULIAR PROPERTIES OF THE PLANT TAXONOMY AT THE HERBARIUMMUSEUM DEPARTMENT PHARMACEUTICAL AND NATURAL SCIENCES FIRST MOSCOW STATE MEDICAL UNIVERSITY NAMED AFTER SECHENOV - SAMYLINA IA; ERMAKOVA VA; STRELIAEVA AV; KARTASHOVA NV (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Department of Pharmaceutical and Natural Sciences of Sechenov First Moscow State Medical University offers students herbarium which should be attributed to special herbaria, namely the collection contains medicinal plants that are well known as official medicine and are widely used in folk medicine. The herbarium provides samples of medicinal plants for the formation of knowledge, practical skills of students of the pharmaceutical faculty. More than 7000 copies of herbarium sheets are offered for the work of students. Methods: Herbarium samples were identified and selected according to the engage thematic plan: Medicinal plants containing essential oils, cardiac glycosides, saponins, polysaccharides, phenolic glycosides, coumarins, lignans, flavonoids, tannins, anthracene derivatives, vitamins, fatty oils, and different groups of biologically active substances. In addition, the department made a small collection of the rare herbarium, which presents medicinal plants widely used in homeopathy, which is used for conducting elective discipline. The wide research of different branches of the medicinal plan was made with the help of pharmacognosy department. The study was carried out with an objective to estimate the need for each herbarium by topic Results: The herbarium fund was formed by the staff of the pharmacognosy department for many years on the basis of the approved pharmacognosy program. The collection is used for research by students – to perform diploma, qualifying works, and teachers to prepare teaching aids, and pharmacopeia articles develop and conduct research. The number of herbarium specimens is stored in the main fund – more than 5000. 240 species of medicinal plants belonging to 104 families are represented.